Textbook multigrid efficiency for the incompressible Navier–Stokes equations: high Reynolds number wakes and boundary layers - Thomas, James L.; Diskin, Boris; Brandt, Achi (Computers & fluids, 2001)
Textbook multigrid efficiencies for high Reynolds number simulations based on the incompressible Navier–Stokes equations are attained for a model problem of flow past a finite flat plate. Elements of the full approximation scheme multigrid algorithm, including distributed relaxation, defect correction, and boundary treatment, are presented for the three main physical aspects encountered: entering flow, wake flow, and boundary layer flow. Textbook efficiencies, i.e., reduction of algebraic errors below discretization errors in one full multigrid cycle, are attained for second order accurate simulations at a laminar Reynolds number of 10,000.